Analisis Efektivitas Pajak Hotel Dalam Upaya Penerimaan Pajak Daerah Kota Bekasi Pada Masa Pandemi Covid-19 - Fransiska Jenery Toyo; Dwikora Harjo (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
in this study was the Bekasi BAPENDA office. The results showed that in 2018 and 2019 the hotel tax had decreased so that it could be said to be less effective and in 2020 it had increased so that it could be said to be effective in hotel tax revenue due to the lack of honesty and truthfulness of taxpayers in paying and reporting hotel tax and the lack of registered Taxpayers' awareness and compliance to pay their tax obligations in accordance with applicable regulations. That way the hotel tax never Hotel tax is a tax on services provided by the hotel. The phenomenon in this study was that hotel tax revenue had not reached the target. It was because of the high competition of star hotels with other cities, the lack of hotel visitors, and taxpayers who did not abide to their tax obligations properly and correctly. This study was conducted with the aim of analyzing the effectiveness of hotel taxes in the effort to increase regional tax in Bekasi during the COVID-19 pandemic along with the obstacles and efforts made by the Regional Revenue Agency (BAPENDA). This study used a descriptive qualitative research method. The data collection methods in this study were observation, interviews, and documentation. The study location reached the target, it could be seen from the data that in 2018, only 72.06% of the target was realized, 66.11% in 2019, and 96.77% in 2020. Efforts are being made to the Regional Revenue Agency to be more responsive in resolving problems from taxpayers so that no more obstacles occur related to hotel tax collection.